Des ruines et des corps pour penser le monde : un entretien avec Melvin Charney - Bénichou, Anne (Ciel variable, 2005)
Abstract In the early 1970s, Melvin Charney began a work in progress, UN DICTIONNAIRE..., a collection of press-agency photographs, published in newspapers, in which buildings and cities involved in current events appeared. Following the attack of September 11, 2001, Charney ended UN DICTIONNAIRE..., devoting the ultimate series to the World Trade Center. In this interview, conducted in March 2005, the photographs of the attack serve as a point of entry to the body of work as a whole. They also provide a pretext for reflection on two important issues in UN DICTIONNAIRE...: ruins as a figure of contemplation, and human bodies and their interaction with the built world as a paradigm for social relationships.